A time motion analysis of bouldering style competitive rock climbing. - White, D.; Olsen, P. D. (The Journal of Strength and Conditioning Research, 2010)
Limited research has been performed on competitive bouldering. The aim of this study was to quantify the movement dynamics of elite boulder climbers. Six climbers were filmed during a national competition consisting of 5 novel climbing problems or routes. Two problems were randomly selected and film footage was analyzed using Kandle Swinger Pro software to determine type and duration (seconds) of bouldering movements. All subjects provided consent, and the study had ethical approval. The mean +/- SD were determined for number of attempts per problem, duration of attempt, time on hold, and time to reach between holds. Exercise:recovery ratios were also calculated. On average, climbers attempted a problem 3.0 +/- 0.5 times, with an attempt lasting 28.9 +/- 10.8 seconds and rest periods of 114 +/- 31 seconds between attempts. Average time gripping holds was 7.9 +/- 1.3 seconds, with approximately 0.5 +/- 0.1 seconds recovery between reaching for holds. The exercise-to-recovery ratio was ~1:4 for attempting a problem and ~13:1 for forearm muscles during climbing. The exercise-to-recovery ratios allow sufficient time for recovery during and after a problem. However, the prolonged contraction of forearm muscles indicates the importance of strength and endurance in these muscles. Video analysis was found to be a useful tool for the quantification of movement characteristics of competitive elite boulders. Data collected could be utilized in the design of sport-specific tests and training programs. Future research could examine a larger number of athletes and problems and help develop performance tests and training interventions for bouldering.